A Computational workflow for the identification of the potent inhibitor of type II secretion system traffic ATPase of Pseudomonas aeruginosa. (October 2018) - Arifuzzaman, Md.; Mitra, Sarmistha; Jahan, Sultana Israt; Jakaria, Md.; Abeda, Tahmina; Absar, Nurul; Dash, Raju
Graphical abstract: Abstract: Bacterial type II secretion system has now become an attractive target for antivirulence drug development. The aim of the present study was to characterize the binding site of the type II secretion system traffic ATPase GspER of Pseudomonas aeruginosa, and identify potent inhibitors using extensive computational and virtual screening approaches. Initially, the designed platform focused on the evolutionary relationship of ATPase GspER of P. aeruginosa, followed by protein-protein interaction network analysis to characterize its function. In addition, homology modeling, virtual screening and molecular dynamics simulation have been performed to identify potent hits and understand the ligand binding properties of ATPase GspER. According to the evolutionary relationship, high level of genetic change was observed for P. aeruginosa, bearing orthology relationships with P.alcaligenes and P.otitidis. Concurrently, the binding site analysis represented residue Gly268, Ser267, Thr270, Thr271and Lys269 in Walker A motif directly formed hydrogen bonds with the ATP, which modulates the function of ATPase GspER in the secretion process, is also validated by the molecular docking analysis and molecular dynamics simulation. Furthermore, ZINC04325133 is one of the most potent hits has been identified from virtual screening approach followed by molecular dynamics simulation and MM-GBSA binding energy analysis. These results may provide new knowledge for the development of novel therapeutic strategies against P. aeruginosa, as well as inhibiting secretion system process of a wide range of gram-negative bacteria.